Methods of analysis and estimation of risks at the enterprises of non‐financial sphere of Latvia - Voronova, Irina (Journal of Business Economics and Management, 2008)
The author considers the problems of analysis and assessment of risks at the enterprises of non‐financial sphere basing on tactical standards of risk management. The author studies the development and impact of the theory of economic cycles on the system of risks in entrepreneurship of Chizhevsky's and Kondratjev's temporary cycles that are at the same time space cycles. The author expresses their attitude to the opportunity of using autogenetic and risks identification. As‐trolinguistics studies the nature of changes in macroeconomic environment on the basis of information about the mutual position of the solar system's planets in the process of their motion. This paper discusses how variety of scope methods may be applied for assessment of the profile of risks at the enterprise.First published online: 14 Oct 2010